Gut Microbiome rewiring via fecal transplants: Uncovering therapeutic avenues in Alzheimer’s disease models - Prabhat Upadhyay; Sudhir Kumar; Anurag Tyagi; Aayush Raj Tyagi; Tarun Barbhuyan; Sarika Gupta (BMC Neuroscience)
Abstract Background Emerging evidence implicates the gut microbiome in Alzheimer’s disease (AD) pathogenesis, yet the underlying mechanisms remain elusive. This study elucidates the bidirectional relationship between gut microbiota and AD using fecal microbiota transplantation (FMT) in a mouse model. Result Through meticulous experimentation, we conducted reciprocal FMT between AD (5xFAD) and healthy (C57BL/6) mice to unravel the impact of gut microbiome alterations on cognitive function and neuroinflammation. FMT from 5xFAD to C57BL/6 mice induced profound memory impairment and cognitive deficits, accompanied by elevated inflammatory cytokine levels, oxidative stress markers, and systemic inflammation, as evidenced by increased plasma cytokines. Conversely, transplanting healthy microbiota into 5xFAD mice yielded remarkable behavioral improvements, including enhanced spatial memory performance in the Morris water maze, directly correlating with cognitive recovery. Our findings underscore the pivotal role of the gut microbiome in AD pathogenesis and offer a promising therapeutic avenue. Conclusion Targeted modulation of the gut microbiome through strategies like FMT may offer potential benefits in Alzheimer’s disease by influencing neuroinflammation, oxidative stress, and cognitive function. This comprehensive study provides novel insights into the gut-brain axis dynamics and paves the way for innovative microbiome-based interventions in AD management.